2018
DOI: 10.1101/lm.047308.118
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement signaling of punishment versus relief in fruit flies

Abstract: Painful events establish opponent memories: cues that precede pain are remembered negatively, whereas cues that follow pain, thus coinciding with relief are recalled positively. How do individual reinforcement-signaling neurons contribute to this "timing-dependent valence-reversal?" We addressed this question using an optogenetic approach in the fruit fly. Two types of fly dopaminergic neuron, each comprising just one paired cell, indeed established learned avoidance of odors that preceded their photostimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 97 publications
10
45
0
Order By: Relevance
“…In adult Drosophila, a single trial of odor preceding electroshock punishment or sugar reward can establish aversive or appetitive associative memory, respectively (Tully and Quinn 1985;Beck et al 2000;Colomb et al 2009;Scheunemann et al 2013). In addition, onetrial learning can be demonstrated upon pairing odor with the optogenetic activation of subsets of dopaminergic neurons innervating the mushroom body in adult flies (Aso and Rubin 2016;König et al 2018).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…In adult Drosophila, a single trial of odor preceding electroshock punishment or sugar reward can establish aversive or appetitive associative memory, respectively (Tully and Quinn 1985;Beck et al 2000;Colomb et al 2009;Scheunemann et al 2013). In addition, onetrial learning can be demonstrated upon pairing odor with the optogenetic activation of subsets of dopaminergic neurons innervating the mushroom body in adult flies (Aso and Rubin 2016;König et al 2018).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…For the memory assays, we followed the procedures described in König et al (2018), unless mentioned otherwise. Flies were loaded into a small transparent tube in a custom-made set-up (CON-ELEKTRONIK, Greussenheim, Germany) and were trained and tested at 23-25°C and 60-80% relative humidity.…”
Section: Adult Behaviormentioning
confidence: 99%
“…To ensure a withinexperiment error rate below 5%, a Bonferroni-Holm (BH) correction for multiple comparisons was employed (Holm, 1979). Sample sizes (biological replications) were estimated based on previous studies with small to medium effect sizes (König et al, 2018;Weiglein et al, 2019). None of the specific experiments reported here had previously been performed in our laboratory, although the basic behavioral paradigms are regularly used.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as mammalian nociceptors send information to the brain via dorsal horn neurons in the spinal cord (Purves et al 2012), insect nociceptors synapse onto neurons that reach the brain (e.g., larval D. melanogaster; Gerhard et al 2017). Although the entire nociceptive pathway has not yet been delineated in any insect, it is known that nociceptive information is processed in two higher-order integratory areas, the mushroom bodies (Waddell 2013;Konig et al 2018) and the central complex (Hu et al 2018). These two areas are among the most complex in the insect brain, and are key for navigation, learning, memory, and other complex cognitive tasks (Barron and Klein 2016; Kinoshita and Homberg 2017).…”
Section: Neurobiology Of Nociception and Painmentioning
confidence: 99%